Je parle pas la langue 1 - Noëlle MATHIS (E-REA)
This text contains traces of the languages that I have heard along my way and that I continue to hear. It reads like an archipelago of fragments to be visited, like islets of (ac)knowledge(ment). It cuts a path in the silent hollows of writing and forgetting across several landscapes. Fragmentation seemed the best writing style as, to quote Roland Barthes recalling Gide, “incoherence is preferable to order that distorts”. The fragments come one after the other, accompanying the hesitations, from one language to another, sending the compass points flying, the flesh of the languages inflamed. Within the languages are folds that have been neglected, traced, reconciled.The fragments are threads of different kinds and from diverse times. They weave together the origin of writing and the origin of sensation; they utter what the body has retained of the echo of the passing presence of each language: the body is where vibration originates; they tell us that we are palimpsests – a complex canvas composed of numerous strata; they come from the night, from silence, from childhood. They also derive from texts I have read and from writing tasks in creative writing workshops that I have designed and facilitated, as well as from independent texts written over the years.From a past impression engraved in the body, through the work of writing, I create a memory. “It (writing) doesn’t so much transcribe the past as create it, by organizing it into a coherent form that it (the past) barely had before it.” I both know and do not know. Knowledge arises and presents itself as the “creation” of knowledge that was hitherto unavailable or unrevealed, and which is illuminated in the act of bringing forth memory. What will the reader hear of this as they read?